Characterization of a Membrane-Associated Trimeric Low-pH-Induced Form of the Class II Viral Fusion Protein E from Tick-Borne Encephalitis Virus and Its Crystallization - Stiasny, Karin (American Society for Microbiology, 2004)
The interaction of a dimeric membrane anchor-free form of the envelope protein E (sE dimer) from tick-borne encephalitis virus with liposomes at acidic pH levels leads to its conversion into membrane-inserted sE trimers. Electron microscopy shows that these trimers have their long dimensions along the threefold molecular axis, which is oriented perpendicularly to the plane of the membrane, where the protein inserts via the internal fusion peptide. Liposomes containing sE at their surface display paracrystalline arrays of protein in a closely packing arrangement in which each trimer is surrounded by six others, suggesting cooperativity in the insertion process. sE trimers, solubilized with nonionic detergents, yielded three-dimensional crystals suitable for X-ray diffraction analysis.